Efficiency and Ownership Structure: Evidence from Rural Banks in Indonesia - Jatmiko, Wahyu (International Journal of Economics, Management and Accounting, 2017)
This paper aims at examining whether ownership structure, which is represented by ownership concentration and type of ownership, affects the technical efficiency of both Islamic and conventional rural banks in Indonesia. First, this study estimates the efficiency score of Islamic and conventional rural banks using Stochastic Frontier Analysis (SFA). The findings suggest that the gap of efficiency level holds among the Islamic Rural Banks (BPRS), yet unobservable in the case of their conventional counterparts (BPR). Management of BPRS is under a big question as the results also indicate that the Islamic microfinance institutions’ inefficiency is getting more severe over time. Second, by using Generalized Linear Model (GLM), this study points out that ownership concentration can explain the inefficiency of BPRS. Relationship between ownership and efficiency appears in cubic polynomial, instead of traditional linear form. It shows that expropriation and alignment effects are jointly embedded in the BPRS. This allows derivation of minimum and maximum turning point of BPRS ownership, which would be very beneficial for policy recommendations.